Strengthening Qur’anic Teaching Skills through Training in the Qur’anic Reading and Writing Method at Tadika Al Fikh Orchard - Ina Zainah; Fitria Ningsih (Yayasan Rahmat Islamiyah, 2026)
This community service activity aimed to strengthen educators’ Qur’anic teaching skills through training in the Qur’anic reading and writing method at Tadika Al Fikh Orchard. Teaching the Qur’an to early childhood learners requires effective, interactive, and age-appropriate methods to ensure that the learning process can be carried out optimally. However, some educators still experience limitations in implementing engaging and systematic Qur’anic learning methods. This activity was carried out through stages of observation, material presentation, demonstrations, direct practice, and evaluation. The training materials included Qur’anic reading techniques, methods of teaching Qur’anic reading and writing, classroom management, and interactive learning strategies for early childhood education. The results of the activity showed improvements in participants’ understanding and skills in teaching Qur’anic reading and writing effectively. In addition, participants became more confident in creating active, enjoyable, and religious learning environments. Through this training activity, it is expected that the quality of Qur’anic learning at Tadika Al Fikh Orchard will continue to improve sustainably.